Remapping Black Germany : New Perspectives on Afro-German History, Politics, and Culture - Lennox, Sara (Book collections on Project MUSE., 2016)
In 1984 at the Free University of Berlin, the African American poet Audre Lorde asked her Black, German-speaking women students about their identities. The women revealed that they had no common term to describe themselves and had until then lacked a way to identify their shared interests and concerns. Out of Lorde's seminar emerged both the term "Afro-German" (or "Black German") and the 1986 publication of the volume that appeared in English translation as Showing Our Colors: Afro-German Women Speak Out. The book launched a movement that has since catalyzed activism and scholarship in Germany.--